miR-24 Regulates Apoptosis by Targeting the Open Reading Frame (ORF) Region of FAF1 in Cancer Cells - Qin, Wenming (Public Library of Science, 2010)
BACKGROUND: microRNAs (miRNAs) are small noncoding RNAs that regulate cognate mRNAs at the post-transcriptional stage. Several studies have shown that miRNAs modulate gene expression in mammalian cells by base pairing to complementary sites in the 3′-untranslated region (3′-UTR) of the target mRNAs. METHODOLOGY/PRINCIPAL FINDINGS: In the present study, miR-24 was found to target fas associated factor 1(FAF1) by binding to its amino acid coding sequence (CDS) region, thereby regulating apoptosis in DU-145 cells. This result supports an augmented model whereby animal miRNAs can exercise their effects through binding to the CDS region of the target mRNA. Transfection of miR-24 antisense oligonucleotide (miR-24-ASO) also induced apoptosis in HGC-27, MGC-803 and HeLa cells. CONCLUSIONS/SIGNIFICANCE: We found that miR-24 regulates apoptosis by targeting FAF1 in cancer cells. These findings suggest that miR-24 could be an effective drug target for treatment of hormone-insensitive prostate cancer or other types of cancers. Future work may further develop miR-24 for therapeutic applications in cancer biology.